Copenhagen Burnout Inventory - student version: adaptation and transcultural validation for Portugal and Brazil - Campos,Juliana Alvares Duarte Bonini (2013)
The Copenhagen Burnout Inventory for college students (CBI-S) was adapted to the Portuguese language and its reliability and validity studied in a sample of both Brazilian (n=958) and Portuguese (n=556) college students. The confirmatory factor analysis of the CBI-S showed good fit but two items were removed since they lack individual reliability (λ<.50). The new structure showed a good fit on 2/3 of the total sample and was invariant in the other 1/3 of the sample. The CBI-S factor weights were not invariant in the Brazilian and Portuguese samples. Internal consistency as well as convergent, discriminant and concurrent validity were good. The Portuguese CBI-S showed adequate reliability and validity but did not show cross-cultural validity.